2023
DOI: 10.1007/s00701-023-05850-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiplatelet and anticoagulant medication use on injury severity and mortality in patients with traumatic brain injury treated in the intensive care unit

Juho Vehviläinen,
Jyri J. Virta,
Markus B. Skrifvars
et al.

Abstract: Background Antiplatelet and anticoagulant medication are increasingly common and can increase the risks of morbidity and mortality in traumatic brain injury (TBI) patients. Our study aimed to quantify the association of antiplatelet or anticoagulant use in intensive care unit (ICU)–treated TBI patients with 1-year mortality and head CT findings. Method We conducted a retrospective, multicenter observational study using the Finnish Intensive Care Consortium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, our findings show that anticoagulant and/or antiplatelet treatment did not affect the 90-day mortality rate. A recent retrospective study in Austria found that a 1-year increase in mortality can be attributed to both anticoagulants and antiplatelets [ 40 ]. However, this study also considered severe TBI.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings show that anticoagulant and/or antiplatelet treatment did not affect the 90-day mortality rate. A recent retrospective study in Austria found that a 1-year increase in mortality can be attributed to both anticoagulants and antiplatelets [ 40 ]. However, this study also considered severe TBI.…”
Section: Discussionmentioning
confidence: 99%